Microbial induced corrosion in French concept of nuclear waste underground disposal. (September 2014) - Féron, D.; Crusset, D.
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of this paper is to give a short overview of how the bacteria, that may influence the corrosion behaviour of metals and alloys, are taken into account in the French concept of geological repository. It is important to underline that microbial induced corrosion is not a new corrosion phenomena but the presence of bacteria may modify (increase or decrease) anodic or cathodic corrosion reactions. In aerobic conditions, high corrosion rates may be obtained due to the bio-oxidation of pyrites. Under anaerobic conditions (longer period), bacteria may have negative (localised corrosion) or positive (consumption of hydrogen) effects. The mixed conditions (with and without oxygen) may be the most dangerous period for localised corrosion of metals and alloys due to the coupling and galvanic corrosion phenomena enhanced by aerobic and anaerobic bacteria. The first conclusions lead to consider that MIC is a 'short term' issue rather than a long term one.